2007
DOI: 10.1007/s00421-007-0625-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind inter-individual differences in lung diffusing capacity

Abstract: We measured diffusing capacity (DLCO), alveolar membrane properties (D (m)), capillary lung volume (V (c)), and alveolar volume (V (A) ) in 20 healthy subjects (12 males; age 32.4 +/- 13 (SD); BMI 21.7 +/- 3; non smokers) at total lung capacity (TLC) and at approximately 80, 60, and 40% TLC. In all subjects, D (m) increased with lung volume, the increase being significantly greater for higher values of D (m)(TLC): the inter-individual differences can be interpreted by a greater number of alveolar units coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Instead, anatomical interpretations of the present results are based on previous studies 48 and should be treated with caution. Similarly, although a reduction in SpO 2 has been thought to be related pulmonary O 2 diffusion capacity 1,2 , a previous study found greater inter-individual differences in the alveolar-capillary membrane diffusing capacity and the pulmonary capillary blood volume, which are subcomponents of total lung diffusion capacity with an inspiration of different concentration of O 2 (20-40-60% O 2 ) 35 . Similar results (i.e., greater inter-indvidual differences in lung diffusion capacity) were found under hypobaric hypoxia at rest 36 and during sub-maximal exercise 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, anatomical interpretations of the present results are based on previous studies 48 and should be treated with caution. Similarly, although a reduction in SpO 2 has been thought to be related pulmonary O 2 diffusion capacity 1,2 , a previous study found greater inter-individual differences in the alveolar-capillary membrane diffusing capacity and the pulmonary capillary blood volume, which are subcomponents of total lung diffusion capacity with an inspiration of different concentration of O 2 (20-40-60% O 2 ) 35 . Similar results (i.e., greater inter-indvidual differences in lung diffusion capacity) were found under hypobaric hypoxia at rest 36 and during sub-maximal exercise 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this point becomes relevant when balanced against an increase in cells metabolic requirement, namely the increased oxygen demand, as in exercise, as well as in conditions causing a limitation to oxygen delivery (environmental hypoxia and cardio-pulmonary disorders). Recent work from our group revealed considerable inter-individual differences in the adaptive response of the air-blood barrier to work in normoxia and hypoxia 13 and further the adaptations correlated with the morpho-functional phenotype of the air-blood barrier 4 .…”
Section: Introductionmentioning
confidence: 71%
“…After surfactant instillation, in preterm, alveolar compliance increased dramatically in line with an increase in average alveolar size and a decrease in alveolar size distribution (Cattarossi et al, 2010). A greater alveolar perfusion was demonstrated in humans at low lung distending pressure (Miserocchi et al, 2008) and, in particular, for P d < 2 cmH 2 O in experimental animal (Godbey et al, 1995). Thus, the decrease in P d can justify the reported improvement in oxygenation index following surfactant replacement therapy by a parallel increase in diffusive and convective conductance for oxygen (Piiper and Scheid, 1981).…”
Section: The Functional Advantage Related To a Decreased Lung Distendmentioning
confidence: 89%